2023
DOI: 10.3389/fendo.2023.1183525
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endogenous oxytocin and vasopressin levels and the Prader-Willi syndrome behaviour phenotype

Lauren J. Rice,
Josephine Agu,
C. Sue Carter
et al.

Abstract: BackgroundOxytocin and vasopressin systems are altered in Prader Willi syndrome (PWS). However, investigations into endogenous oxytocin and vasopressin levels as well as clinical trials evaluating the effect of exogenous oxytocin on PWS symptoms have had mixed results. It is also unknown whether endogenous oxytocin and vasopressin levels are associated with certain PWS behaviours.MethodWe compared plasma oxytocin and vasopressin and saliva oxytocin levels in 30 adolescents and adults with PWS to 30 typically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Besides oxytocin, researchers have identified decreases in several other neuropeptides relevant to PWS (Table 1). Lower levels of AVP, which regulates the tonicity of body fluids and affects behaviors related to social interactions, have been reported in Magel2null mice and PWS patients [65,73,202]. Orexin/hypocretin, which is important for sleep regulation, food intake, and energy balance, is also altered in PWS patients and mouse models (Table 1) [153,203].…”
Section: Oxytocin and Other Neuropeptidesmentioning
confidence: 95%
“…Besides oxytocin, researchers have identified decreases in several other neuropeptides relevant to PWS (Table 1). Lower levels of AVP, which regulates the tonicity of body fluids and affects behaviors related to social interactions, have been reported in Magel2null mice and PWS patients [65,73,202]. Orexin/hypocretin, which is important for sleep regulation, food intake, and energy balance, is also altered in PWS patients and mouse models (Table 1) [153,203].…”
Section: Oxytocin and Other Neuropeptidesmentioning
confidence: 95%
“…Common symptoms of PWS include cognitive, endocrine and behavioral dysfunction, including irritability, which often manifests itself as temper tantrums [ 55 ]. Rice et al [ 56 ] found that, in patients with the 15q11-q13 PWS subtype, salivary OXT levels were inversely correlated with symptom severity, suggesting that OXT deficiency may play a role in the PWS symptomatology. Further studies have connected OXT deficiency with aberrant behaviors observed in patients with PWS [ 57 ].…”
Section: Introductionmentioning
confidence: 99%